Efektivitas Supervisi Akademik Pengawas Sekolah Terhadap Kualitas Pembelajaran Pendidikan Agama Islam Pada Sekolah Dasar - Wagito; Khairuddin Lubis (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the effect of school supervisors’ academic supervision on the quality of Islamic Religious Education (PAI) learning in elementary schools in Pakpak Bharat Regency. The study employed a quantitative approach using a descriptive correlational method. The population consisted of 62 PAI teachers, with a sample of 35 respondents selected through proportional random sampling. Data were collected using questionnaires and documentation and analyzed using descriptive statistics and simple linear regression. The results showed that academic supervision achieved a score of 74%, categorized as effective, while the quality of PAI learning reached 76%, categorized as good. The regression analysis yielded a tcalculated value of 4.122 > ttable of 2.034, with a significance value of 0.000 < 0.05. The R² value of 0.340 indicates that academic supervision contributed 34.0% to the quality of Islamic Religious Education learning. These findings emphasize the importance of developing a regionally adaptive supervision model to improve the quality of Islamic Religious Education learning.